Economic implications of ACOSOG Z0011 trial application into clinical practice at the European Institute of Oncology. Issue 10 (October 2021) - Mattar, Denise; Di Filippo, Antonio; Invento, Alessandra; Radice, Davide; Burcuta, Marius; Bagnardi, Vincenzo; Magnoni, Francesca; Santomauro, Giorgia; Corso, Giovanni; Mazzarol, Giovanni; Viale, Giuseppe; Sacchini, Virgilio; et al.
Abstract: Background and objectives: The American College of Surgeons Oncology Group (ACOSOG) Z0011 trial demonstrated that in clinically node-negative women undergoing breast-conserving therapy (BCT) and found to have metastases to 1 or 2 sentinel nodes, sentinel lymph node biopsy (SLNB) alone resulted in rates of local control, disease-free survival, and overall survival equivalent to those seen after axillary lymph node dissection (ALND), but with significantly lower morbidity. Application of the Z0011 guidelines resulted in fewer ALNDs without affecting locoregional recurrence or survival. Changes in practice inevitably affect health care costs. The current study investigated the actual impact of applying the Z0011 guidelines to eligible patients and determined the costs of care at a single institution. Patients and methods: We compared axillary nodal management and cost data in breast cancer patients who met the Z0011 criteria and were treated with BCT and SLNB. Patients were allocated into two mutually exclusive cohorts based on the date of surgery: pre-Z0011 (June 2013 to December 2015) and post-Z0011 (June 2016 to December 2018). Results: Of 3912 patients, 433 (23%) and 357 (17.6%) patients in the pre- and post-Z0011 era had positive lymph nodes. ALND decreased from 15.3% to 1.57% in the post-Z0011 era. The mean overall cost of SLNB in the pre-Z0011 cohort was €1312 per patient, while that for SLNB with completion ALND was €2613. Intraoperative frozen section (FS) use decreased from 100% to 12%. Omitting the FS decreased mean costs from €247 to €176. The mean total cost in the pre-Z0011 cohort was €1807 per patient, while in the post-Z0011 cohort it was €1498. The application of Z0011 resulted in an overall mean cost savings of €309 for each patient. Conclusions: Application of the Z0011 criteria to patients undergoing BCT at our institution results in more than half a million Euro cost savings.